SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PEMBELIAN PRODUK DENGAN METODE TOPSIS (Studi Kasus: CV. Cahaya Mustika) - Debora Rose M; Soetam Rizky Wicaksono (RJOCS (Riau Journal of Computer Science), 2017)
CV. Cahaya Mustika is a company works in procurement industry sells many varied product with different categories. Each product marketed and sold by this company has lots of variation from different aspects needed by customer and differed by many brands.  This is the company’s competitive advantage from having diverse product, however this also means company should manage supplier list from different product categories and different product specification. Based on the problem faced by CV. Cahaya Mustika which is to decide from which supplier should they buy the products so they could sell the products with more profit and on time based on customer demand, the writer propose a decision support system using Multiple Objective Decision Making (MODM) to help them giving a solution and advise in taking decision of choosing supplier using Technique Others Reference By Similiarity To Ideal Solutions (TOPSIS). This technique is based on the concept where the chosen alternative not only has the nearest distance with the positive ideal solution, but also has the furthest distance from negative ideal solution.